O ICMS como instrumento de indução ao consumo sustentável - Silva, Nayara Crispim da (2018)
The present dissertation concentrates an analysis on the constitutional principles that validate the ICMS as an instrument of induction to the sustainable consumption. In order to present how such practice it’s inserted in the Brazilian legal system, it addresses the fundamentals of extrafiscality, brings concepts related to taxation with environmental purposes and indicates relevant aspects about the graduation of the tax burden of this indirect tax. Then, through an incursion into the principle of equality, it demonstrates how the constitutional norms justifies the resultant differentiated tax treatment among consumers. It emphasizes, in particular, the interpretive reasoning from which it’s observed the semantic coherence between the principles of selectivity based on the essentiality of goods and services (article 155, § 2, III) and of the defense of the environment in the economic order (article 170, VI), culminating in the idea of an "environmental essentiality". In the end, it exposes practical application of the theoretical bases constructed